EFEK BLIND FEEDING UNTUK MENINGKATKAN PERTUMBUHAN POST LARVA UDANG VANAME KEPADATAN TINGGI DAN PENGARUHNYA TERHADAP KUALITAS AIR [The Effect of Blind feeding to Increase Post Larva Growth of High-density Vaname Shrimp and Their Effect on Water Quality] - Fahrur, Mat; Syah, Rachman; Makmur, Makmur; Suwoyo, Hidayat Suryanto; Asaad, Andi Indra Jaya; Taukhid, Imam (Berita Biologi, 2023)
Blind feeding is a feed dosage of feeding shrimp cultivation that is carried out without looking at the shrimp biomass conditions for the first 30 days. The goal is to ensure that shrimp get adequate feed intake in the early stages of growth, yet blind feeding often has an impact on the decline in water quality as a result of overfeeding. The study aimed to evaluate the effect of the blind feeding method on the growth of vaname shrimp (Litopenaeus vannamei) and water quality. The treatments to be tested were the quantity of feed: (a) 123.5 kg/100,000 shrimp; (b) 148.2 kg/100,000 shrimp; (c) 172.9 kg/100,000 shrimp; (d) 197.6 kg/100,000 shrimp; and (e) 222.3 kg/100,000 shrimp. The dose range of blind feeding referred to the habits applied by the cultivators in the field. The shrimp used was PL 12 with a density of 1,000 individuals/m3, which were maintained for 30 days in an aquarium container of 50 x 40 x 30 cm or a volume of 50 liters. The feed was given four times a day at 8.00, 12.00, 16.00, and 20.00. The results of the study showed that the blind feeding feed dosage had a significant effect on the absolute growth of shrimp and total ammonia nitrogen (P < 0.05). The blind feeding treatment (c), which was 172.9 kg/100,000 shrimps, produced the best growth with a lower total ammonium nitrogen so it is recommended that it be applied in shell cultivation in the first 30 days of maintenance.